Mutant combinations of lycopene ɛ‐cyclase and β‐carotene hydroxylase 2 homoeologs increased β‐carotene accumulation in endosperm of tetraploid wheat (Triticum turgidum L.) grains. Issue 3 (18th November 2021) - Yu, Shu; Li, Michelle; Dubcovsky, Jorge; Tian, Li
Summary: Grains of tetraploid wheat ( Triticum turgidum L.) mainly accumulate the non‐provitamin A carotenoid lutein—with low natural variation in provitamin A β‐carotene in wheat accessions necessitating alternative strategies for provitamin A biofortification. Lycopene ɛ‐cyclase (LCYe) and β‐carotene hydroxylase (HYD) function in diverting carbons from β‐carotene to lutein biosynthesis and catalyzing the turnover of β‐carotene to xanthophylls, respectively. However, the contribution of LCYe and HYD gene homoeologs to carotenoid metabolism and how they can be manipulated to increase β‐carotene in tetraploid wheat endosperm (flour) is currently unclear. We isolated loss‐of‐function Targeting Induced Local Lesions in Genomes (TILLING) mutants of LCYe and HYD2 homoeologs and generated higher order mutant combinations of lcye‐A, lcye‐B, hyd‐A2, and hyd‐B2 . Hyd‐A2 hyd‐B2, lcye‐A hyd‐A2 hyd‐B2, lcye‐B hyd‐A2 hyd‐B2, and lcye‐A lcye‐B hyd‐A2 hyd‐B2 achieved significantly increased β‐carotene in endosperm, with lcye‐A hyd‐A2 hyd‐B2 exhibiting comparable photosynthetic performance and light response to control plants. Comparative analysis of carotenoid profiles suggests that eliminating HYD2 homoeologs is sufficient to prevent β‐carotene conversion to xanthophylls in the endosperm without compromising xanthophyll production in leaves, and that β‐carotene and its derived xanthophylls are likely subject to differential catalysis mechanisms in vegetative tissues and grains. Carotenoid and gene expression analyses also suggest that the very low LCYe‐B expression in endosperm is adequate for lutein production in the absence of LCYe‐A . These results demonstrate the success of provitamin A biofortification using TILLING mutants while also providing a roadmap for guiding a gene editing‐based approach in hexaploid wheat.